(untitled) (Journal of Economic Research & Business Administration, 2016)
The crisis of the economy, business entities are deficient funding sources, as commercial banks restricted lending to them. Crisis situations are forcing enterprises, companies seek new ways to solve this problem. One solution is the use of factoring services. Today, factoring services are relevant and popular service – more and more companies are adopting and using factoring mechanism for settlements with partners. Western countries practice proves the effectiveness of the factoring even in certain sectors of the economy has replaced the traditional lending services. In many countries factoring has become one of the main instruments for financing business. In Kazakhstan, the factoring as a business financing tool is only beginning to develop and win their share of the financial market. In this article the features of factoring services, the analysis of the state of the factoring market in the Republic of Kazakhstan and the identified problems and prospects of development.